Economic Value of Fosaprepitant-Containing Regimen in the Prevention of Chemotherapy-Induced Nausea and Vomiting in China: Cost-Effectiveness and Budget Impact Analysis - Xu, Xinglu; Bao, Yuwen; Xu, Kai; Zhang, Zhuolin; Zhao, Ningli; Li, Xin (Frontiers in Public Health, 2022)
Objective: The purpose of this study was to evaluate the cost-effectiveness and budget impact of fosaprepitant (FosAPR)-containing regimen for the prevention of chemotherapy-induced nausea and vomiting (CINV) among patients receiving high emetogenic chemotherapy (HEC) from the Chinese payer’s perspective. Methods: A decision tree model was established to measure the five-day costs and health outcomes between the APR-containing regimen (aprepitant, granisetron, and dexamethasone) and FosAPR-containing regimen (fosaprepitant, granisetron, and dexamethasone). Clinical data were derived from a randomized, double-blind controlled trial on Chinese inpatients who received HEC. Quality-adjusted life-years (QALYs) were used to estimate the utility outcomes and the incremental cost-effectiveness ratio (ICER) was calculated to assess the economics of FosAPR. A static budget impact model was developed to assess the impact of FosAPR as a new addition to the National Reimbursement Drug List (NRDL) on the medical insurance fund within three years in Nanjing, China. Results: Compared with APR, FosAPR had a mean health-care savings of ￥121.56 but got a reduction of 0.0001815 QALY, resulting in an ICER of ￥669926.19 per QALY. Deterministic sensitivity analysis revealed that the cost of APR was the most influential factor to the ICER. The cost of FosAPR and the complete control rate of the delayed period also had a high impact on the results. According to the probabilistic analysis, the acceptability of FosAPR was more than 80% when the Chinese willingness-to-pay (WTP) was ￥215,999. FosAPR would lead to a 3-year medical insurance payment increase of ￥1.84 million compared with ￥1.49 million before FosAPR entered NRDL in Nanjing. The total budget increased with a cumulative cost of ￥694,829 and covered an additional 341 patients who benefited from FosAPR in Nanjing. Deterministic sensitivity analysis showed that the model of budget impact analysis was stable. Conclusion: FosAPR had a similar treatment effect to APR but was cost-effective in China at the current WTP threshold. The total budget of medical insurance payments of Nanjing slightly increased year by year after the inclusion of FosAPR. Its inclusion in the NRDL would be acceptable and also expand the coverage of patients who benefited from FosAPR.